Portuguese legislation on intangible cultural heritage and inventories - Carvalho, Ana (2013)
The article analyses the Portuguese legislation about Cultural Heritage, namely the approach towards Intangible Cultural Heritage (ICH), a new category promoted by the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage (2003). Furthermore, it presents general considerations regarding inventories in the Portuguese scene, considering the importance of identifying ICH as a preliminary step in order to develop safeguarding strategies.